Pengaruh Servicescape Dan Kualitas Pelayanan Terhadap Customer Emotion Melalui Kepuasan Konsumen - Anggraini, Sesilia; Iskandar, Donant Alananto (STREAMING, 2023)
This study aims to determine how much influence servicescape and service quality on customer emotion through customer satisfaction at the coffee square. This research is a quantitative approach using the SPSS Statistics 20 program with a total sample of 185 respondents whose people live in Jadebek who have eaten or drank at Alun Alun Coffee by using nonprobability sampling and purposive sampling techniques. The results of this research t test shows that servicescape directly affects customer emotion with a significance value of 0.001 <0.05 and a t value of 3.463> 1.973 so that servicescape is very important for Alun-Alun Coffee. Service quality variables have a direct effect on customer emotion with a significance value of 0.000> 0.05 and a t value of 10.745> 1.973 which means that partially service quality variables have a positive effect on customer emotion at Alun Alun Coffee. Meanwhile, servicescape directly affects customer emotion through customer satisfaction with a significance value of 0.000> 0.05 and a t value of 4.598> 1.973. The benefit of this research for Alun Alun Coffee is as input or evaluation in order to maintain and improve facilities and service quality to compete with other competitors.